Role of Parental Attachment Styles in Moderating Interaction Between Parenting Stress and Perceived Infant Characteristics - Quintigliano, Maria; Trentini, Cristina; Fortunato, Alexandro; Lauriola, Marco; Speranza, Anna Maria (Frontiers in Psychology, 2021)
By employing the transactional model of development and focusing on the multifactorial nature of parenting, this study aimed to 1) examine whether important risk factors, particularly mothers’ insecure attachment styles and parenting stress contribute to their perception of their infants’ characteristics and 2) explore whether attachment styles moderate the relationship between parenting stress and perceived infants’ characteristics. The participants included 357 mothers who had one-year-old infants. They all completed three self-report instruments: Parenting Stress Index–Short Form (PSI-SF), Attachment Style Questionnaire (ASQ), and First-Year Inventory (FYI). Although the latter was originally developed to determine the risk of autism in one-year-olds, it was employed in this study to measure an infant’s characteristics in two domains: social communication and sensory regulatory functions. Multiple regression analyses revealed that one of the PSI-SF dimensions, Parent–Child Dysfunctional Interaction, may contribute to mothers’ perceptions of their children’s social communication abilities, whereas the attachment style does not. Other multiple regression analyses have showed that different dimensions of parenting stress may contribute to mothers’ perceptions of their sensory regulatory functions to which attachment styles could significantly contribute. Finally, moderation analyses revealed that avoidance attachment and anxious attachment styles could moderate the relationship between parenting stress and perceived infant’s characteristics in the two domains.